2014
DOI: 10.1287/mksc.2013.0840
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Loyalty Reward in Dynamic Price Discrimination

Abstract: International audienceIn a dynamic model with overlapping generations of consumers, we study duopolistic competition when firms can price discriminate, at each period, between their previous customers and the consumers that they have never served. Long-term contracts are not enforceable. In (Markov-perfect) equilibrium, one firm charges higher prices to its past customers than to its new customers, as past customers have revealed their strong preferences for the firm; the other firm, however, rewards its previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 39 publications
(53 reference statements)
1
26
0
1
Order By: Relevance
“…As in the present paper, Liu and Serfes (2004) have found that moving from no discrimination (no information) to discrimination is bad for industry profits and good for consumer surplus. However, conditional on the availability of information, they have 14 For other recent papers on BBPD and customer recognition, see also Caillaud and De Nijs (2011), Chen and Pearcy (2010), Esteves (2010), Esteves and Vasconcelos (2014), Esteves and Reggiani (2014), Gehrig et al (2011Gehrig et al ( , 2012, Ghose and Huang (2009), Ouksel and Eruysal (2011, 2013. 15 They define targetability as a firm's ability to predict the preferences and purchase behaviors of individual consumers.…”
Section: Related Literaturementioning
confidence: 99%
“…As in the present paper, Liu and Serfes (2004) have found that moving from no discrimination (no information) to discrimination is bad for industry profits and good for consumer surplus. However, conditional on the availability of information, they have 14 For other recent papers on BBPD and customer recognition, see also Caillaud and De Nijs (2011), Chen and Pearcy (2010), Esteves (2010), Esteves and Vasconcelos (2014), Esteves and Reggiani (2014), Gehrig et al (2011Gehrig et al ( , 2012, Ghose and Huang (2009), Ouksel and Eruysal (2011, 2013. 15 They define targetability as a firm's ability to predict the preferences and purchase behaviors of individual consumers.…”
Section: Related Literaturementioning
confidence: 99%
“…For other recent papers on BBPD, see also Caillaud and De Nijs (), Chen and Pearcy (), Esteves and Reggiani (), and Gehrig et al. (, ).…”
mentioning
confidence: 99%
“…Personalized pricing and mass customization will transform each individual to a market segment of one. Behavior-based price discrimination implies charging a personalized price to each customer, according to their past purchase history, location, and other finegrained data (Caillaud and De Nijs, 2014). Technological tools have made easier for companies to apply personalized pricing.…”
Section: Future Perspective 75 Years 2020-2095mentioning
confidence: 99%